SGLT-2 Inhibitors and Metabolic Outcomes: A Primary Data Study Exploring the Microbiota–Diabetes Connection - Nicoleta Mihaela Mindrescu; Cristian Guja; Viorel Jinga; Sorina Ispas; Antoanela Curici; Rucsandra Elena Danciulescu Miulescu; Andreea Nelson Twakor; Anca Mihaela Pantea Stoian (Metabolites, 2025)
Background: The gut microbiota plays a critical role in metabolic health and type 2 diabetes mellitus (T2DM). Alterations in microbial composition may influence glycemic control and systemic inflammation. Materials and methods: In this single-center, randomized study, 60 adults with T2DM receiving metformin were evaluated biologically and received either empagliflozin or sitagliptin. Demographic, metabolic, and lifestyle data were collected. Gut microbiota profiling was conducted at two timepoints to assess changes in bacterial and fungal taxa. Blood glucose, HbA1c, and inflammation markers were analyzed longitudinally. Results: Both treatment groups showed significant improvements in glycemic control. Median fasting glucose decreased from 132 to 123 mg/dL (p = 0.046) in the sitagliptin group and from 131 to 114 mg/dL (p = 0.025) in the empagliflozin group. Median HbA1c levels declined significantly in both groups, with a greater reduction in the empagliflozin group (p = 0.001 vs. p = 0.049). The microbiota analysis revealed an increase in beneficial bacteria (e.g., Bifidobacterium spp. and Lactobacillus spp.) and a decrease in pro-inflammatory taxa (Escherichia coli and Streptococcus spp.). Notably, empagliflozin was associated with a more pronounced microbiota rebalancing and a significant decline in fungal overgrowth (e.g., Candida spp.; p = 0.034). Conclusions: Treatment with sitagliptin and empagliflozin led to improved glycemic outcomes and partial restoration of gut microbial balance in T2DM patients. Empagliflozin showed superior efficacy in modulating both glycemia and dysbiosis.